Foresight in Higher Education Institutions: Evidence from Poland - Joanna Ejdys; Alicja Eva Gudanowska; Katarzyna Halicka; Anna Kononiuk; Andrzej Magruk; Joanicjusz Nazarko; Lukasz Nazarko; Danuta Szpilko; Urszula Widelska (Foresight and STI Governance)
The rapid transformation of the socioeconomic, political, and technological context predetermines changes in the expectations for higher education institutions that face numerous profound challenges. In order to survive and develop under changing conditions, universities need to drastically rethink their development strategies. The paper substantiates the effectiveness of using foresight for these purposes, which is confirmed by the experience of the project on the development of scenarios for the Faculty of Engineering Management (FEM) of Bialystok Technical University (Poland) for the period up to 2035. This enquiry has resulted in compiling four alternative visions for FEM. By analyzing them one can gain valuable knowledge on both preferable and less-favored alternatives, which on the one hand suggest which actions may lead to their realization, but on the other,indicate specific actions that may lead to the abandonment of undesirable paths in favor of the most conducive vision.